A very short, fairly interesting and reasonably cheap book about studying organizations - Grey, Christopher (Los Angeles ; London : SAGE, 2013)
This is an essential introduction to the critical analysis of organizations which can be thoroughly recommended to all students coming to this subject new. In a writing style which is lucid, witty and informative, Grey shows how the study of organizations is central to all our lives. He rescues organization studies from managerial hype and places it back at the centre of our understanding of the social, ethical and political dilemmas of the twenty-first century.
Introduction : Why studying organizations matter to me -- Bureaucracy and scientific management -- Human relations theory and people management -- Organizational culture and self-management -- Post-bureaucracy and change management -- The new capitalism and the strange fates of management -- Conclusion : Why should studying organizations matter to you?
Previous edition: Los Angeles, Calif.; London: SAGE, 2009.
Includes bibliographical references (pages 149-158) and index.
Keywords: Organizational behavior; Management; Management; Organizational behavior